2009
DOI: 10.1002/mnfr.200800013
|View full text |Cite
|
Sign up to set email alerts
|

The effects of green tea (–)‐epigallocatechin‐3‐gallate on reactive oxygen species in 3T3‐L1 preadipocytes and adipocytes depend on the glutathione and 67 kDa laminin receptor pathways

Abstract: Green tea (-)-epigallocatechin-3-gallate (EGCG) is known as to regulate obesity and fat cell activity. However, little information is known about the effects of EGCG on oxidative reactive oxygen species (ROS) of fat cells. Using 3T3-L1 preadipocytes and adipocytes, we found that EGCG increased ROS production in dose- and time-dependent manners. The concentration of EGCG that increased ROS levels by 180-500% was approximately 50 muM for a range of 8-16 h of treatment. In contrast, EGCG dose- and time-dependentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 52 publications
(86 reference statements)
3
43
0
Order By: Relevance
“…It is intriguing that prion protein also induces intracellular ROS production via NADPH oxidase (71). It has also previously been reported that a high concentration (50 M) of EGCG induced generation of lethal levels of ROS dependent on 67LR (72). It is important to distinguish this previous study from ours.…”
Section: Discussionmentioning
confidence: 57%
“…It is intriguing that prion protein also induces intracellular ROS production via NADPH oxidase (71). It has also previously been reported that a high concentration (50 M) of EGCG induced generation of lethal levels of ROS dependent on 67LR (72). It is important to distinguish this previous study from ours.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, we hypothesized that sugiol would induce ROS production. Many prior studies reported that natural compounds induce intracellular ROS to kill cancer cells [14][15][16]. Therefore, we investigated whether sugiol induced ROS generation in DU145 cells.…”
Section: Sugiol Interacts With Transketolase and Induces Ros Generationmentioning
confidence: 99%
“…The high ROS levels in cancer cells renders these cells more susceptible to oxidative stress-induced cell death, which can be exploited for selective cancer therapy [13]. Many known natural compounds, such as curcumin, EGCG, and resveratrol, generate ROS to destroy cancer cells [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, resveratrol, curcumin and epigallocatechin-3-gallate are all reported to act as insulin sensitizing agents, reverse hyperglycemia, hyperlipidemia and other symptoms linked to obesity [87][88][89][90] . These natural compounds may initially cause a depolarization of mitochondrial membrane potential and ROS production, then activate the Nrf2 system to exert subsequent protective responses [19,[91][92][93] . Furthermore, these plant-derived polyphenols are electrophilic and can modulate the reactive cysteine residues in Keap1 molecules, leading to a dissociation of Nrf2 from the Nrf2-Keap complex and increasing the free Nrf2 level [94,95] .…”
Section: Nrf2 System As a Potential Drug Target For Diabetes Treatmentmentioning
confidence: 99%